Youdale, Roy. Using Computers in the Translation of Literary Style: Challenges and Opportunities. New York/London: Routledge, 2020, 242 p. - Raimundo Ednardo Soares de Souza Júnior (Cadernos de Tradução, 2022)
Youdale, Roy. Using Computers in the Translation of Literary Style: Challenges and Opportunities. New York/London: Routledge, 2020, 242 p.